Community-based lung cancer screening with low-dose CT in China: Results of the baseline screening. (March 2018) - Yang, Wenjia; Qian, Fangfei; Teng, Jiajun; Wang, Huimin; Manegold, Christian; Pilz, Lothar R.; Voigt, Weiland; Zhang, Yanwei; Ye, Jianding; Chen, Qunhui; Han, Baohui; ,
Highlights: A community-based screening for lung cancer in a Chinese population. LDCT led to a 74.1% increase in detecting early-stage lung cancer. Non-smoking related risk factors of lung cancer in the Chinese population. Abstract: Objectives: To investigate whether low-dose computed tomography (LDCT) screening is capable of enhancing the detection rate of early-stage lung cancer in high-risk population of China with both smoking and non-smoking related factors. Methods: From 2013–2014, eligible participants with high-risk factors of lung cancer were randomly assigned to a screening group or a control group with questionnaire inquiries. Any non-calcified nodules or masses with longest diameters of ≥4 mm identified on LDCT images were considered as positive. Results: A total of 6717 eligible participants were randomly enrolled to a study group (3550 to LDCT screening and 3167 to standard care). 3512 participants (98.9%) underwent LDCT screening, and 3145 participants (99.3%) received questionnaire inquiries. A positive screening result was observed in 804 participants (22.9%). In the two-year follow-up period, lung cancer was detected in 51 participants (1.5%) in the LDCT group versus 10 (0.3%) in the control group (stage I: 48 vs 2; stage II to IV or limited stage: 3 vs 8), respectively. Early-stage lung cancer was found in 94.1% vs 20%, respectively. Conclusions: Compared to usual care, LDCT led to a 74.1% increase in detecting early-stage lung cancer. This study provides insights about the non-smoking related risk factors of lung cancer in the Chinese population.